USEFULNESS OF LASER PHOTOCOAGULATION IN MANAGING ASYMPTOMATIC EYES OF EALES` DISEASE - Ishaq, Mazher; Niazi, Muhammad Khizar (Journal of Ayub Medical College Abbottabad, 2002)
Background: Eales disease is an idiopathic obliterative vasculopathy that commonly affects the peripheral retina of healthy young males characterized by recurrent vitreous haemorrhage. We did this study to evaluate the usefulness of prophylactic scatter photocoagulation in asymptomatic eyes of patients presenting with vitreous haemorrhage due to Eales Disease. Methods: Ninety nine patients with Eales’ Disease demonstrable on the basis of 3 mirror fundus exam and Florescein Fundus Angiography with vitreous haemorrhage underwent either Pan retinal photocoagulation or vitrectomy in a span of 3 years. Their fellow asymptomatic eyes were grouped on the basis of their visual acuity, fundus findings and FFA picture. Group A comprising of forty-three cases underwent PRP whereas forty-three cases of Group B were not given any treatment. These cases were followed for at least three years (range 38-42 months). Results: Out of the forty-three cases of group A, thirty-nine (83.82%) showed visual improvement as compared to only nine cases in Group-B (p<0.001). Vitreous involvement was present in only 16 cases in Group-A as compared to 33 cases in Group-B. Twenty-eight cases of Group-B showed signs of persistence of disease process in the retina compared to 13 cases in Group-A (p<0.005). Conclusion: Prophylactic photocoagulation is an effective method of controlling the secondary complications in asymptomatic eyes of Eales disease especially if managed at an early stage. Regular checkup of peripheral retina by triple mirror examination should be performed in all asymptomatic fellow eyes of Eales disease to detect the disease process at an early stage and prevent further complications. KEYWORDS: Eales disease, Photocoagulation, Retinal neovascularization, Vitreous haemorrhage.